FAKTOR RISIKO DAN PENANGANAN NYERI PERSALINAN - Agustin Dwi Syalfina (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
Labour is a process of stretching, cervical dilation and contraction to remove the fetus and placenta. The process causes maternal pain. This pain is subjective so that there is a difference of perception between women maternity. Labor pain is influenced by obstetric, invidual, environmental, social and cultural support factors. Pain management methods consist of pharmacologic and nonpharmacologic. Relaxation of long breath is one non-pharmacological method that is useful to provide peace and quiet so as to reduce anxiety in the mother, if the anxiety of the mother is reduced or even not anxious then the pain of labor will be reduced. So in this study aims to analyze the factors that affect labor pain at the time of first active phase and the effect of long respiratory relaxation on the incidence of labor pain during first active phase. This study uses cross sectional design with a large sample of 35 respondents with the condition meet the criteria of inclusion and exclusion. Instrumen uses check list and processed by editing, coding, entry and tabulating. Data analysis with SPPS for windows 16 chi square test. Factors that have significant effect on labor pain in the first active phase are age (p value = 0,006; PR = 1,06; 95% CI = 0,50-0,24) and race (p value = 0,008; PR = 18,45 95% CI = 3,35-1,61). Long respiratory relaxation showed a significant effect on labor pain during the fisrt active phase (p value = 0,00006; PR = 12,36; 95% CI = 1,11-3,70). Long breath relaxation is a non-pharmacological method for reducing labor pain. Suggestion of health worker giving guidance of relaxation technique since pregnancy through pregnant mother class.